The Effect of the Responsive Writing Strategy on the Achievement of Second Intermediate Grade Students in Social Studies - Amjad Nazim Ali, Rese; Alaa Ibrahim Saehan Hamad, Asst. Prof. Dr. (lark, 2025)
The present study aims to investigate the effect of the responsive writing strategy on the academic achievement of second intermediate grade students in the subject of social studies. The researchers adopted the quasi-experimental design with a post-test for academic achievement. The study population consisted of second intermediate grade students in public intermediate and secondary day schools affiliated with the Directorate of Education in Al-Muthanna, Al-Warka district. Al-E’tilaf Intermediate School was randomly selected to conduct the experiment. The school includes three sections for the second intermediate grade; section (A) was randomly chosen to represent the experimental group, which was taught using the responsive writing strategy, while section (B) represented the control group and was taught using the conventional method. The total sample consisted of 66 students, with 33 students in each group. To measure academic achievement, a test was constructed comprising 40 items: 35 multiple-choice questions and 5 short-answer essay questions, with the validity and reliability of the test confirmed. The researchers used the t-test for two independent samples to analyze the following variables: chronological age (in months), parents’ academic achievement, and mid-year scores in social studies. The results revealed that the students in the experimental group who were taught using the responsive writing strategy significantly outperformed those in the control group who were taught using the traditional method in terms of academic achievement.
Keywords: Responsive writing strategy, academic achievement